A micro-elimination approach to addressing hepatitis C in Turkey - Ramazan Idilman; Homie Razavi; Sarah Robbins-Scott; Ulus Salih Akarca; Necati Örmeci; Sabahattin Kaymakoglu; Bilgehan Aygen; Nurdan Tozun; Rahmet Güner; Hurrem Bodur; Jeffrey V. Lazarus (BMC, 2020)
Abstract Background In 2016, WHO passed the Global Health Sector Strategy on Viral Hepatitis (GHSS), calling for its elimination by 2030. Two years later, Turkey approved a strategy to reach the WHO targets. This study reports new national prevalence data, breaks it down by subpopulation, and models scenarios to reach HCV elimination. Methods Literature was reviewed for estimates of HCV disease burden in Turkey. They were discussed with stakeholders and used as inputs to develop a disease burden model. The infected population was estimated by sequelae for the years 2015-2030. Three scenarios were developed to evaluate the disease burden in Turkey: a Base 2017 scenario, representing the current standard of care in Turkey; an increased treatment scenario, representing the impact of improved access to DAAs; and a WHO targets scenario, which meet the WHO GHSS viral hepatitis targets of a 65% reduction in mortality and 90% diagnosis rate of the infected population by 2030. Results At the beginning of 2017, 271,000 viremic infections were estimated. Of these, 58,400 were diagnosed and 10,200 treated. Modelling results showed that, with the current treatment paradigm in Turkey, by 2030 the total number of viremic HCV infections would decline by 35%, while liver-related deaths, hepatocellular carcinoma (HCC), and decompensated cirrhosis would decrease by 10-25%. In the increased treatment scenario, by 2030 viremic HCV infections would decrease by 50%; liver-related deaths, HCC and decompensated cirrhosis would decrease by 45-70%. In the WHO targets scenario, HCV infections would decrease by 80%; sequelae would decrease by 80-85%. Data on disease burden in micro-elimination target subpopulations are largely unavailable. Conclusions To meet the WHO Global Health Sector Strategy targets for the elimination of HCV, Turkey needs to increase treatment. Better data are needed as well as countrywide access to DAAs.